Contextual constraint and N + 2 preview effects in reading. Issue 3 (March 2013) - Radach, Ralph; Inhoff, Albrecht W.; Glover, Lisa; Vorstius, Christian
Extracting linguistic information from locations beyond the currently fixated word is a core component of skilled reading. Recent debate on this topic is focused on the question of whether useful linguistic information can be extracted from more than one (parafoveally visible) word to the right of a fixated word (N). The current study examined this issue through the use parafoveal previews with a short and high-frequency next (N + 1) word, as this should increase the opportunity for the extraction of useful information from the subsequent (N + 2) word. Pairs of N + 2 words were selected so that contextual constraint was either high or low. Using saccade contingent display manipulations, preview of a N + 2 target word during word N viewing consisted of either a visually dissimilar nonword or a word. The results revealed a substantial drop in fixation probability for word N + 1 when the N + 2 preview was masked with a nonword. Furthermore, the masking of word N + 2 influenced its viewing duration even when word N + 1 was fixated prior to word N + 2 viewing. These results provide compelling evidence for the view that the linguistic processing can encompass more than one word at a time.